Produção de biossorvente magnetizado à base de biopolímeros do tipo polissacarídeo, para remoção de cromo (VI) de efluentes industriais - Costa, Antonio Wilson Macedo de Carvalho (2017)
The growth of anthropogenic actions, especially industrial development and urbanization, has increased the release of heavy metals in the environment, including hexavalent chromium, Cr (VI), requiring, as a matter of urgency, new processes for pollutants removal, among which are the adsorption processes, which are the focus of this work. Biosorption is an efficient, economical, high selectivity and low energy consumption technique. The main objective of this work was the production of a biosorbent from the crop residues of Cocos nucifera, enhancing it with superparamagnetic properties, as a viable technical and economical alternative, able to adsorb hexavalent chromium ions, Cr (VI), applicable to the treatment of industrial wastewater, expanding pollution control strategies and minimizing environmental impacts. Thus, low concentration coprecipitation routes for the synthesis of nanoparticle (NPs) were proposed, conveying magnetic property to the Cocos nucifera biomass. During the biosorption of hexavalent chromium ions, Cr (VI), the saturation conditions (equilibrium) and the kinetic parameters were evaluated to determine the maximum removal capacity and equilibrium time for the biosorption, besides the optimum conditions for pH, initial concentration, biosorbent content, particle size (grain size), stirring velocity and temperature, providing the fitting of equilibrium models and kinetic constants determination. The biosorbents were characterized by scanning electron microscopy techniques with dispersive energy spectroscopy (SEM/EDS), Fourier transform infrared spectrometry (FT-IR), X-ray diffraction (EDX), X-ray fluorescence with dispersive energy (FR-X/WD), thermogravimetric analysis (TGA), magnetization measurements, zero load point analysis (pCZ), and specific surface analysis through the Brunauer, Emmet and Teller (BET) method. The leachate effluent obtained in the production of the magnetized fibers was characterized through the parameters biochemical oxygen demand (BOD), chemical oxygen demand (COD), total organic carbon (TOC) and pH. The characterization of biosorbents and the determination of kinetic and equilibrium parameters provided the main mechanisms of the biosorption process, giving arise to a possible application on an industrial scale, helping to solve serious environmental problems.